2000
DOI: 10.1161/01.hyp.35.1.103
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Phosphorylation of Human Platelet Plasma Membrane Ca 2+ -ATPase in Hypertension

Abstract: Abstract-IntracellularCa 2ϩ is increased in the platelets of hypertensive individuals. Previously, we demonstrated that platelet plasma membrane Ca 2ϩ -ATPase (PMCA) activity inversely correlates with diastolic blood pressure and that inhibition of this Ca 2ϩ pump could explain the elevation of cytosolic Ca 2ϩ in hypertension. More recently, we discovered that PMCA is phosphorylated on tyrosine residues during thrombin-stimulated platelet aggregation and that this phosphorylation causes inhibition of PMCA acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Changes in the activity and/or distribution of PMCA might have a crucial impact on platelet functions. Our earlier finding that platelet PMCA is phosphorylated on tyrosine residues and inhibited in hypertensive individuals resulting in increased cytosolic Ca 2ϩ demonstrates the importance of this protein for proper platelet function (14).…”
Section: Plasma Membrane Ca 2ϩ -Atpase Binding To Platelet Cytoskeletonmentioning
confidence: 91%
See 1 more Smart Citation
“…Changes in the activity and/or distribution of PMCA might have a crucial impact on platelet functions. Our earlier finding that platelet PMCA is phosphorylated on tyrosine residues and inhibited in hypertensive individuals resulting in increased cytosolic Ca 2ϩ demonstrates the importance of this protein for proper platelet function (14).…”
Section: Plasma Membrane Ca 2ϩ -Atpase Binding To Platelet Cytoskeletonmentioning
confidence: 91%
“…Isolation and Analysis of Platelet Subcellular Fractions-Platelet concentrates were obtained from the American Red Cross (Louisville, KY) and prepared as described previously (14). Briefly, platelets were isolated by centrifugation and resuspended in Tyrode's-HEPES buffer containing 138 mM sodium chloride, 2.9 mM potassium chloride, 12 mM sodium bicarbonate, 0.36 mM sodium phosphate, 5.5 mM glucose, 1.8 mM calcium chloride, 0.4 mM magnesium chloride, 10 mM HEPES, pH 7.4, 0.1 mM aspirin, and 0.2 unit/ml apyrase.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, mechanisms relevant to dysfunctional Ca 2+ homeostasis in hypertension have also been investigated. Ca 2+ pump-specific tyrosine phosphorylation may effect pump inhibition and elevate intracellular Ca 2+ levels in hypertensive individuals [14]. In support of this concept, thrombin-stimulated Ca 2+ -ATPase phosphorylation levels were 2.5-fold greater in platelets from hypertensive than normotensive subjects.…”
Section: Platelet Metabolites and Ca 2+ Pump Phosphorylationmentioning
confidence: 81%
“…In support of this concept, thrombin-stimulated Ca 2+ -ATPase phosphorylation levels were 2.5-fold greater in platelets from hypertensive than normotensive subjects. Blackenship et al [14] suggested Ca 2+ pump inhibition increased intracellular Ca 2+ and placed these individuals at greater risk for thrombotic events.…”
Section: Platelet Metabolites and Ca 2+ Pump Phosphorylationmentioning
confidence: 99%
“…Removal of cytosolic Ca 2+ and maintenance of a low [Ca 2+ ] c is mediated by Ca 2+ extrusion, mainly by the plasma membrane Ca 2+ -ATPase (PMCA), and sequestration into the intracellular stores (Rosado and Sage, 2000a). Ca 2+ mobilization in platelets is altered in a number of pathologies, such as type 2 diabetes mellitus (Saavedra et al, 2004) or hypertension (Blankenship et al, 2000), leading to cardiovascular disorders associated to platelet hyperaggregability. In platelets from type 2 diabetic subjects Ca 2+ mobilization and extrusion are altered (Saavedra et al, 2004;Rosado et al, 2004b).…”
Section: Overview Of Platelet Ca 2+ Homeostasismentioning
confidence: 99%